Planning Method of Diffusion Capability for the Multiple Resources of User-side Including Distributed Photovoltaic Access. Issue 1 (January 2021) - Huang, Jia-qi; Sang, Zi-xia; He, Ji-feng; Yan, Jiong; Wang, Si-cong; Yang, Dong-jun; Lei, He; Wang, Ya-lei
Abstract: High penetration of distributed renewable energy is the trend of future power and energy systems. Under the background of retail electricity market reform, retail price mechanism is of great significance to facilitate large-scale integration and consumption of user-side renewable energies. Considering the adoption of renewable energy is essentially the diffusion process of technological innovation, we presented an evaluation method for measuring the diffusion capability of distributed photovoltaic with the retail price mechanism. Firstly, based on the residential double-step tariff structure, the decision models were proposed for energy transactions between retailers and customers using Ramsey pricing theory. Secondly, by introducing the methodology of system dynamics, the market feedback mechanism between the electricity price design and the integration capacity of distributed photovoltaic was analyzed, thus the evolutionary model of distributed photovoltaic dynamic diffusion under the price policy was established. Finally, the criterion of stable diffusion of distributed photovoltaic based on Lyapunov function was developed in this paper.